The Flat feet Increased The Postural Instability on The Elderly in Nursing Home - Fathia Larasati; Titi Moertolo; Kirana Anggraeni (Indonesian Journal of Physical Medicine & Rehabilitation, 2017)
Introduction: Flat feet or flatfeet are the postures that have a low medial longitudinal arch. The prevalence ofFlat feet was 10-25% of adults population. The lower feet arch might have an impact on body sway have duringstanding posture. Furthermore, increasing of the postural sway could have the higher risk of fall in elderly, thathas a prevalence of 30-50%. The aim study to find the correlation between the Flat feet posture with posturalstability, to prevent the risk of fall in the elderly.Method: This design was observational cross-sectional study. The study conducted in the elderly nursing home.The posture was examined by ink feet print on white paper. The Tinetti Balance Assessment assessed the posturalstability.Result: The subjects were 84 elderly, mostly were 60-74 years old, and 46 (54,8%) were female. The mostprevalence of the postural stability was the low risk of fall (59,5%). The frequency of Flat feet was 26 (31%).There was a relationship between Flat feet with postural stability in elderly (p = 0,020).Conclusion: There was a correlation between the Flat feet and the postural stability on elderly in the nursinghome.Keywords: Flat feet, postural stability, elderly